Adult Attachment in Early Adulthood with Divorced Parents - Amara Nezia; Cempaka Putrie Dimala; Dinda Aisha (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Individuals from divorced families have a higher risk compared to those from intact families when entering adulthood. These individuals tend to feel less secure in forming attachments with others during early adulthood. This study aims to examine the adult attachment patterns of early adults with divorced parents in Karawang Regency. This descriptive quantitative research involves 100 early adults in Karawang, using non-probability sampling. Data collection was conducted through an online questionnaire distribution. Adult attachment was measured using the Revised Adult Attachment Scale (RAAS) with a Likert scale from 1 to 5. The results show that the dominant attachment type is anxiety attachment, held by 51% of early adults with divorced parents, followed by depend on attachment (26%) and close attachment (23%). Hypothesis testing reveals no significant differences between gender and attachment patterns, but there are significant differences between the age groups of 20-25 years (transition from adolescence to adulthood) and 26-40 years (early adulthood), as well as between the age at which parents divorced, specifically early childhood (2-6 years) and late childhood (7-12 years). No significant differences were found based on relationship status (dating, engaged, or married). These findings suggest that anxiety attachment patterns are more prevalent in individuals who experienced parental divorce at a younger age, and both age and parental divorce experiences influence early adulthood attachment patterns. Individu yang berasal dari keluarga yang bercerai memiliki resiko yang lebih besar dibanding individu dengan keluarga yang utuh ketika memasuki usia dewasa. Individu tersebut memiliki kecenderungan untuk merasa kurang aman dalam menjalin kelekatan dengan orang lain di saat dewasa awal. Penelitian ini bertujuan untuk melihat gambaran adult attachment pada dewasa awal dengan orang tua yang bercerai di Kabupaten Karawang. Penelitian kuantitatif deskriptif ini melibatkan 100 dewasa awal di Karawang dengan menggunakan non-probability sampling. Pengumpulan data dilakukan menggunakan penyebaran kuesioner secara daring. Pengukuran adult attachment menggunakan Revised Adult Attachment Scale (RAAS) dengan skala Likert 1 hingga 5. Hasil penelitian ini menunjukkan bahwa tipe anxiety attachment dominan dimiliki oleh dewasa awal dengan orang tua yang bercerai, dengan persentase sebesar 51%, diikuti dengan depend on attachment (26%) dan close attachment (23%). Uji hipotesis menunjukkan tidak ada perbedaan signifikan antara jenis kelamin terhadap pola kelekatan, namun terdapat perbedaan signifikan antara kelompok usia 20-25 tahun (masa transisi remaja menuju dewasa) dan 26-40 tahun (dewasa awal), serta antara usia ketika orang tua bercerai, yakni masa kanak-kanak awal (2-6 tahun) dan masa kanak-kanak akhir (7-12 tahun). Tidak ditemukan perbedaan signifikan berdasarkan status hubungan (berpacaran, tunangan, atau menikah). Temuan ini menunjukkan bahwa pola anxiety attachment lebih tinggi pada individu yang mengalami perceraian orang tua pada usia lebih muda, dan usia serta pengalaman perceraian orang tua mempengaruhi pola kelekatan dewasa awal.